1993
DOI: 10.1001/jama.1993.03500070058029
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of Vasectomy and Prostate Cancer in US Men

Abstract: These results support evidence from other epidemiologic studies that vasectomy increases risk of prostate cancer. A biological mechanism whereby vasectomy influences the rate of prostate cancer may be related to a diminished secretory rate of prostatic fluid following vasectomy, or, alternatively, to the postvasectomy immune response to sperm antigens, which may cross-react with tumor-associated antigens and suppress tumor immunosurveillance mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…The study of Honda et al 16 found the relative risk of prostate cancer was higher among men who had a vasectomy 30 y than among men who had no vasectomy or had a vasectomy less than 30 y. Hayes et al 20 reported a higher risk of prostate cancer for men having had a vasectomy 20 y. Mettlin et al 19 reported an increased risk for men who had a vasectomy 13±18 y prior to a diagnosis of prostate cancer but not among men who had a vasectomy 19±44 y prior. The most recent reports by Giovannucci et al 12,13 similarly note this association. Their retrospective cohort study 13 found a signi®cantly increased relative risk of prostate cancer among men having a vasectomy 20 y prior to a diagnosis of prostate cancer.…”
Section: Introductionmentioning
confidence: 58%
See 4 more Smart Citations
“…The study of Honda et al 16 found the relative risk of prostate cancer was higher among men who had a vasectomy 30 y than among men who had no vasectomy or had a vasectomy less than 30 y. Hayes et al 20 reported a higher risk of prostate cancer for men having had a vasectomy 20 y. Mettlin et al 19 reported an increased risk for men who had a vasectomy 13±18 y prior to a diagnosis of prostate cancer but not among men who had a vasectomy 19±44 y prior. The most recent reports by Giovannucci et al 12,13 similarly note this association. Their retrospective cohort study 13 found a signi®cantly increased relative risk of prostate cancer among men having a vasectomy 20 y prior to a diagnosis of prostate cancer.…”
Section: Introductionmentioning
confidence: 58%
“…The most recent reports by Giovannucci et al 12,13 similarly note this association. Their retrospective cohort study 13 found a signi®cantly increased relative risk of prostate cancer among men having a vasectomy 20 y prior to a diagnosis of prostate cancer. Their prospective cohort study 12 also reported that the strong association between vasectomy and an elevated risk of prostate cancer was even more pronounced among men who had their vasectomy 22 y in the past.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations